Application of Cultural Icons in Local Brand Development Strategies: With Special Reference to Sri Lankan Context - Dissanayake, D.M.R. (Gyan Management Journal, 2010)
Cultural icons of a country or particular ethnic segment reflect the behavioral na_ture of its origin and values. However, most of local value driven brands have been using the cultural aspects to associate their brand values and signifiers. This has been a significant matter whenever there is a huge competition against foreign brands. Researchers selected four cate9ories of products namely biscuits, soaps, toothpastes and telecommunications which are highly concentric to cultural icons to develop brand values. 150 respondents were selected on stratified sampling method. The Principal Component Model of factor analysis had been used to analyze the empirical data. Data analysis reviewed that cultural icons had a significant impact on brand awareness and recalling power. However, it was found that local brand
Keywords: Local brands; Cultural icons; Brand performances; Foreign brands